CFD Analysis of Flow, Pollutant Dispersion and Thermal Effects in Street Canyons - Zakaria, M.S.; Abu Bakar, M.F.A.; Ridhwan, J.; Mohd Hanafi, M.H. (Journal of Engineering and Technology (JET), 2014)
Aim of this study is to investigate the pollutant dispersion inside an urban street canyon so that the understanding of the characteristics of air flow subjected to the dispersion of pollutant can help achieve greater air quality urban areas, sustainably for improving the health and comfort of the people. Using numerical method through Computational Fluid Dynamic Software ANSYS Fluent, a simplified two dimensional street canyon is modeled to simulate the flow of pollutant subjected to building geometry as well as wind speed. The building height and street width were manipulated throughout the study. A series of multiphase analysis were conducted with different building height to street width ratio to examine the pollutant dispersion rate. With the volume fraction gradually decrease from Φ=1 to a certain value that indicates the pollutant has disperse. The result presented the relation between the street canyon geometry and the pollutant dispersion rate, with wider streets proves to have a better pollution dispersion rate as well as when the wind speed is higher. The significant of the study is to see effect of the street canyon geometry to the rate of pollutant dispersion.